An analytical study of some aspects of the technical and tactical aspects in the World Cup for juniors in field hockey - Abu El-Maati, M. T. (World Journal of Sport Sciences, 2011)
This research aims to identify the impact of modified free-hit, by using the self-pass, on the tactic moves of hockey players.Also, it aims to analyze the performance of the German team (first place winner) in this tournament in order to identify the most effective ways for building up, as well as the new roles of playmaker (center half) in the transport and building the attack. The study included a sample of 12 matches for teams of Germany, Netherlands, Singapore and United States in the Juniors World Cup set up in Malaysia, Singapore in 2009. They contained 6 matches for teams of Germany and Netherlands (first and second place in the tournament), 6 games for team of Singapore and United States (before last and last places in the tournament), at the rate of 3 games for each team. The sample chosen for match analysis contained 5 games for the German team (winning the first place) and games of the final and semi final, besides some of the preliminary round matches. the most important result indicated that the second method (pass longissimus) was better than the first method (exchange the ball between the players) in terms of the effectiveness of building up to get the ball to the 25 yards of the competing team, while the first method (exchange the ball between the players) better than the second method (pass longissimus) in the effectiveness of building up to get the ball to the middle of the pitch of the competing team, the more roles the players used in the transport and building up are the roles of playmaker and more roles of playmaker session was a hub mount to lead the attack. The best positions to build the attack for effectiveness of the opposite defense (full press) is the status to use rhombus (1-3), while the best position for effectiveness of attack commonly used to build the opposite defense (3/4court) is the status to use the form Z (2-2) and the best position to use for effectiveness of attack commonly used to build the opposite defense (have court) is cavity (2-2).